Nexus between Sharia Governance and Financial Performance: Evidence from Indonesian Islamic Banking - Hijriah, Hanifiyah Yuliatul; Kholidah, Himmatul; Alkausar, Bani; Laila, Nisful; Al Mustofa, Muhammad Ubaidillah (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
ABSTRACT – This study critically evaluates the effectiveness of Islamic governance on the financial performance of Islamic banks in Indonesia. Due to the absence of regulations defining optimal Sharia Supervisory Board (SSB) structure and qualifications, the research explores the empirical relationship between SSB characteristics and financial performance. Using a quantitative approach, the study analyzes data from 14 Islamic banks over a seven-year period (2014-2020). Multiple regression analysis reveals that SSB size, educational background, and financial/accounting expertise have minimal impact on financial performance. Interestingly, cross-membership on SSBs is found to have a negative effect. These findings, coupled with the observation of SSBs often lacking banking and finance backgrounds, suggest a potential disconnect between Sharia governance and managerial activities. The study advocates for clear and comprehensive regulations to strengthen SSB composition and competence, ultimately promoting the sustainable development of Islamic banking in Indonesia.========================================================================================================ABSTRAK – Hubungan Antara Tata Kelola Syariah dan Kinerja Keuangan: Bukti dari Perbankan Syariah Indonesia. Studi ini secara kritis mengevaluasi efektivitas tata kelola Syariah terhadap kinerja keuangan perbankan syariah di Indonesia. Mengingat belum adanya peraturan yang mengatur struktur minimum dan kualifikasi optimal Dewan Pengawas Syariah (DPS), penelitian ini bermaksud mengkaji secara empiris empiris hubungan antara karakteristik DPS dan kinerja keuangan. Dengan menggunakan pendekatan kuantitatif, penelitian ini menganalisis data dari 14 bank Islam selama tujuh tahun (2014-2020). Hasil analisis regresi berganda menunjukkan bahwa ukuran DPS, latar belakang pendidikan, dan keahlian keuangan dan akuntansi kurang memiliki dampak terhadap kinerja keuangan perbankan syariah. Menariknya, cross-membership pada DPS ditemukan memiliki efek negatif. Temuan ini, ditambah dengan pengamatan terhadap DPS yang seringkali tidak memiliki latar belakang perbankan dan keuangan, menunjukkan potensi keterputusan antara tata kelola Syariah dan aktivitas manajerial. Studi ini merekomendasikan adanya peraturan yang jelas dan komprehensif untuk memperkuat komposisi dan kompetensi DPS, yang pada akhirnya mendorong pengembangan bank syariah yang berkelanjutan di Indonesia.